2018
DOI: 10.7224/1537-2073.2016-079
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes from the Branded Glatiramer Acetate Pregnancy Database

Abstract: These data provide evidence that branded GA exposure during pregnancy seems safe, without teratogenic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 30 publications
1
47
0
1
Order By: Relevance
“…Research undertaken as part of the DMF clinical development program has indicated no increased risk of foetal abnormalities or other adverse pregnancy outcomes relative to the general population when women are exposed to DMF during pregnancy 108 . There is also evidence to show the use of GA during pregnancy is likely to be safe, with no increased risk of congenital abnormalities found for infants prenatally exposed to GA relative to those with no prenatal exposure 109 .…”
Section: Pregnancy Outcomes and Exposure To Ms Disease Modifying Drugsmentioning
confidence: 99%
“…Research undertaken as part of the DMF clinical development program has indicated no increased risk of foetal abnormalities or other adverse pregnancy outcomes relative to the general population when women are exposed to DMF during pregnancy 108 . There is also evidence to show the use of GA during pregnancy is likely to be safe, with no increased risk of congenital abnormalities found for infants prenatally exposed to GA relative to those with no prenatal exposure 109 .…”
Section: Pregnancy Outcomes and Exposure To Ms Disease Modifying Drugsmentioning
confidence: 99%
“…Currently glatiramer is considered a safer option during pregnancy compared to other DMARDs, although its use during this period should only be recommended if the benefit to mother outweighs any risk for the foetus. 5 This appraisal also recommended the use of interferon beta-1b (Extavia) for patients with secondary progressive MS but who continue to have relapses; this is the only treatment currently recommended by NICE for this specific clinical scenario. 6 Retaining the variety of treatment options for patients with relapsing-remitting MS is valuable.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Food and Drug Administration, Copaxone ® is a “Category B” drug, meaning that no risks have been shown in animal fetuses, but there are no well-controlled studies related to human pregnancy. Reports on over 5000 cases of branded Copaxone ® exposure during pregnancy reinforce the lack of teratogenic effects [ 112 , 113 ]. These findings provide important knowledge for better counseling for women with MS who intend to become pregnant and should not forgo the use of DMDs while attempting to conceive.…”
Section: Self-injectable Dmdsmentioning
confidence: 99%